Financial reporting - Alexander, David; Britton, Anne. (London ; New York : International Thomson Business Press, 1999)
This text combines financial accounting theory with an examination of the legal and regulatory framework of accounting. The explanations, interspersed with activities and feedback to stimulate interest in the topics, may be useful for second and third year students of accounting.
Includes bibliographical references and index.
oif 17/03/15
Loan
Keywords: Accounting; Financial statements; Accounting theory